IMPLEMENTASI SISTEM INFORMASI APARATUR DI KANTOR BADAN KEPEGAWAIAN PENDIDIKAN PELATIHAN DAERAH KOTA BEKASI - Muhammad Yunus; Agung Wahyudin; Rahmat Nuryono; Abdul Muis; Mita Widyastuti (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2022)
The Apparatus Information System, abbreviated as SIAP, is a system that manages data and serves employees in the Bekasi City Government on an online basis of the Bekasi City Regional Training Education Personnel Board (BKPPD) to make it easier for employees to get information. Once the importance of employee data management in an organization, improving the quality of personnel management through employee information systems is one of the priorities of e-government. In implementing the development of the human resources information system in Indonesia, a Regulation of the Head of the State Personnel Agency Number 20 of 2008 concerning Guidelines for Utilizing the Personnel Service Application System has been stipulated. Then proceed through the decision of Bekasi Mayor Regulation Number 20 of 2017 concerning Apparatus Information Systems in the Bekasi City Government. This study aims to determine how the implementation of the information system apparatus in the Bekasi City Government and how the obstacles faced in the implementation of the apparatus information system managed by the Bekasi City Regional Civil Service Agency. This research uses qualitative methods and constructivism paradigm by applying data collection techniques through in-depth interviews, observation, and literature study, data analysis techniques using coding, and informant retrieval through purposive sampling. The results of the research show that: (1) The implementation of SIAP in Bekasi City Government is in accordance with the legal basis and SOP (Standard Operational Procedure), (2) the factors that hinder the implementation of SIAP in Bekasi City Government include: unstable internet connection used in managing SIAP, there are restrictions on the use of SIAP access.